Pediatric Extrapulmonary Tuberculosis, One Senter Six Years Experience - Belgin Gülhan; Saliha Kanık Yüksek (Galenos Publishing House, 2020)
INTRODUCTION: To review the clinical, laboratory and epidemiological characteristics of extrapulmonary tuberculosis cases of childhood. METHODS: In this study, patients who were diagnosed as extrapulmonary tuberculosis under the age of 18 in University Of Health Sciences, Ankara Child Health and Diseases Hematology Oncology Training and Research Hospital between 2012-2017 were examined retrospectively. Demographic characteristics, clinical findings, microbiology, imaging information, treatments and disease course of the patients were collected. RESULTS: Extrapulmonary tuberculosis constituted 64% of tuberculosis cases. The female / male ratio was 23/25 and the mean age was 9.3 years. Fifteen patients (31.3%) had peritoneal tuberculosis, 14 patients (29.2%) had tuberculosis lymphadenitis, 6 patients (12.5%) had pleural tuberculosis, 4 patients had bone tuberculosis, 3 patients had BCG lymphadenitis, 3 patients had central nervous system tuberculosis and 1 patient had milier tuberculosis. Thirty-five patients were diagnosed by tissue biopsy. Tuberculin skin test was found to be positive in 17 (36.2%) patients, and 3% of patients had a history of contact with tuberculosis. DISCUSSION AND CONCLUSION: In childhood, extrapulmonary tuberculosis is a disease that should be considered in the presence of suspicious clinical findings. Tissue biopsy is very helpful in the diagnosis of extrapulmonary tuberculosis.